2019
DOI: 10.1186/s12711-019-0471-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feed restriction on the environmental variability of birth weight in divergently selected lines of mice

Abstract: Background Selection of mice for decreased environmental variability of birth weight has achieved higher survivability and larger litter size as a correlated response to canalized selection, which suggests higher welfare and robustness, and animals that are more homogeneous. However, in these studies, animals were not exposed to an environmental challenge. To demonstrate the advantages of this mouse line with a low environmental variability of birth weight, animals from two divergent lines (high a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…However, it was not proven if selection was balanced between the lines, or one of the lines perhaps did not response or the lines had responded with a different magnitude. This is a significant issue, as selection for reducing the variability has been shown to have great benefits, unlike the high line variability [ 12 , 13 , 14 ]. This was possible to check through the control line.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was not proven if selection was balanced between the lines, or one of the lines perhaps did not response or the lines had responded with a different magnitude. This is a significant issue, as selection for reducing the variability has been shown to have great benefits, unlike the high line variability [ 12 , 13 , 14 ]. This was possible to check through the control line.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that this selection criterion had direct effects in other interesting traits in livestock such as litter size, weaning weight, and survival [ 6 ]. As a result of the divergent experiment, two divergent lines were created, with the low line presenting benefits in production [ 12 ], animal welfare [ 6 ], heritability [ 11 ], and robustness traits [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low line animals performed better in reproductive indicators but marked lower BW. This reduction in the individual weight was accompanied by an increase in litter size and survival at weaning (Formoso‐Rafferty et al., 2018) without negative impact in the weaning weight nor in the weight at the beginning of the reproductive age in this mice population (Formoso‐Rafferty et al., 2019). This impact of the selection on body weight seemed to be a consequence of a statistical scale effect, since a lower variability results in a lower mean (Tatliyer et al., 2019), but this did not negatively affect the total litter weight (Formoso‐Rafferty et al., 2016b).…”
Section: Discussionmentioning
confidence: 96%
“…They also showed that this selection criterion directly affected other interesting traits in livestock such as litter size, weaning weight and pup survival (Formoso‐Rafferty et al., 2016b). The experiment led to two divergent lines with the low line presenting benefits in production (Formoso‐Rafferty et al., 2016b), animal welfare (Formoso‐Rafferty et al., 2016a), the increase in heritability due to reduced residual variance (Formoso‐Rafferty et al., 2017) and traits usually considered robustness indicators such as feed efficiency (Formoso‐Rafferty et al., 2018, 2019). However, the implications of uniformity on reproductive longevity are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Also, important was higher reproductive longevity reported with a threefold probability of performing a new parturition in the homogeneous line relative to the heterogeneous line (Formoso‐Rafferty et al, 2022). The advantage of the L‐line is added to the ones already found, such as litter size, weaning weight, and survival, presenting benefits in production (Formoso‐Rafferty et al, 2016b), animal welfare (Formoso‐Rafferty et al, 2016a), heritability (Formoso‐Rafferty et al, 2016b), and robustness traits (Formoso‐Rafferty et al, 2018, 2019).…”
Section: Discussionmentioning
confidence: 99%